Factors Causing Incomplete Medical Records of Covid-19 Patients in Santa Elisabeth Batam City Hospital 2021 - Situmorang, Masriani; Mulyana, Mulyana; Abellya, Abellya (UIMA Press, 2022)
Background: One of the active roles of medical recorders is to determine the quality of health services in hospitals with good and complete data or information from medical records. Outpatient medical record services start from the place of registration until obtaining medical record documents used to obtain health services. Objectives: Objective To find out the factors that cause incomplete filling of medical record files, especially for Covid-19 patients at Santa Elisabeth Hospital in 2021. Methods: Methods The type of research used in this research is research qualitative with a qualitative approach and using the interview method, observation, and questionnaire. Results: The results of the study show that the large workload and time constraints are the main factors for nurses and doctors not filling out completely, and the part of the medical record that is not filled in greatly affects the claim of BPJS or the Ministry of Health. Conclusion: The incompleteness of the medical record form for Covid-19 patients still has obstacles in the element of lack of communication between health care workers, and discipline of officers due to lack of awareness of doctors about the importance of completing medical record files. The workload is quite high, motivation is low, there is no mix, policy, and SOP in the medical record section, lack of socialization about medical record SOP.